2005
DOI: 10.1111/j.1475-3588.2005.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Service Contacts Among the Children Participating in the British Child and Adolescent Mental Health Surveys

Abstract: Method:  A third of the children from the 1999 British Child and Adolescent Mental Health Survey were followed up over 3 years. Parents provided summary information on service contacts for emotional, behavioural and concentration difficulties, with more detailed information being obtained by telephone interview for selected subgroups. Results:  Having a psychiatric disorder predicted substantially increased contact with social services, special educational needs resources, the youth justice system and mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 18 publications
3
68
1
Order By: Relevance
“…The parents identified services used from a checklist consisting of the following categories: • Barriers to services use: Drawing on a list of 15 themes that had emerged from earlier research [6], parents indicated which reasons had stopped them from accessing services in the last 12 months even when concerned with their child's health [12].…”
Section: Methodsmentioning
confidence: 99%
“…The parents identified services used from a checklist consisting of the following categories: • Barriers to services use: Drawing on a list of 15 themes that had emerged from earlier research [6], parents indicated which reasons had stopped them from accessing services in the last 12 months even when concerned with their child's health [12].…”
Section: Methodsmentioning
confidence: 99%
“…Up to a third of children and adolescents attending primary care and paediatric outpatient departments have clinically significant psychopathology 2 3. Only a minority of these children reach specialist mental health services, partly because the presenting complaint is rarely psychological, so their disorders may not be recognised 2 4. Child mental health services may reject inappropriate referrals leading to frustration among referrers and families.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using a pathways to care approach (Goldberg and Huxley 1980) view problem recognition and/or referral from primary care physicians as fundamental in accessing specialized mental health care (e.g., Sayal 2006;Zwaanswijk et al 2005). Parents' problem recognition (Pavuluri et al 1996) and perceived burden have been found to increase the likelihood of a child receiving services, as has receiving a referral from either a primary-care physician or a teacher (Ford et al 2005;Sayal 2004). However, many children/families receive specialized mental health services without being referred, suggesting that the help-seeking process varies across families and does not follow a linear pathway (Farmer et al 2003;Ford et al 2005;Godfrey 1995;Pavuluri et al 1996;Shanley et al 2008;Zwaanswijk et al 2005).…”
mentioning
confidence: 97%
“…and even fewer receive specialized mental health treatment (Hazen et al 2004) such as care at a mental health clinic or agency, or from a mental health professional such as a psychologist, psychiatrist or mental health social worker (Ford et al 2003(Ford et al , 2005Gardner et al 2004;John et al 1995;Zwaanswijk et al 2005). Understanding help-seeking, or the steps through which families move on their way to receiving treatment, may help to close the gap between those children needing and receiving mental health services (Durbin et al 2004;Zwaanswijk et al 2003).…”
mentioning
confidence: 97%